HIV-1 induction of tolerogenic dendritic cells is mediated by cellular interaction with suppressive T cells - Svanberg, Cecilia; Nyström, Sofia; Govender, Melissa; Bhattacharya, Pradyot; Che, Karlhans F.; Ellegård, Rada; Shankar, Esaki M.; Larsson, Marie (Frontiers in Immunology, 2022)
HIV-1 infection gives rise to a multi-layered immune impairment in most infected individuals. The chronic presence of HIV-1 during the priming and activation of T cells by dendritic cells (DCs) promotes the expansion of suppressive T cells in a contact-dependent manner. The mechanism behind the T cell side of this HIV-induced impairment is well studied, whereas little is known about the reverse effects exerted on the DCs. Herein we assessed the phenotype and transcriptome profile of mature DCs that have been in contact with suppressive T cells. The HIV exposed DCs from cocultures between DCs and T cells resulted in a more tolerogenic phenotype with increased expression of e.g., PDL1, Gal-9, HVEM, and B7H3, mediated by interaction with T cells. Transcriptomic analysis of the DCs separated from the DC-T cell coculture revealed a type I IFN response profile as well as an activation of pathways involved in T cell exhaustion. Taken together, our data indicate that the prolonged and strong type I IFN signaling in DCs, induced by the presence of HIV during DC-T cell cross talk, could play an important role in the induction of tolerogenic DCs and suppressed immune responses seen in HIV-1 infected individuals.